Lexical Variation in Regional Modern Standard Arabic. Issue 1 (2nd January 2022) - Azaz, Mahmoud; Alfaifi, Essa
Abstract: Adapting the notions of regional Modern Standard Arabic (Ibrahim 2009; Ryding 2010) and gradience in acceptability judgments (Papadopoulou, Leivada, and Pavlou 2014), this paper teases apart educated native speakers' judgements and lexical preferences in an intricate case of lexical collocations. In this case, one of the two co-occurring words or constituents has two variants rendered in different morphological forms, but they are derived from the same root. The results of an acceptability judgment task showed that educated Saudi Arabian speakers tended to disfavour lexical variants used in Egyptian newspapers and overwhelmingly opted for the variants used in their region when forced to do so. It is argued that although the lexicon of Standard Arabic is relatively stable and governed by substantial regularities and conformities to standard morphological rules, still regional varieties can be differentiated. The dynamic nature of Standard Arabic synchronically and its interaction with Arabic dialects in different regions is discussed.